Hematological, biochemical, and morphological parameters as prognostic indicators for stranded common dolphins (Delphinus delphis) from Cape Cod, Massachusetts, U.S.A. Issue 3 (6th December 2013) - Sharp, Sarah M.; Knoll, Joyce S.; Moore, Michael J.; Moore, Kathleen M.; Harry, Charles T.; Hoppe, Jane M.; Niemeyer, Misty E.; Robinson, Ian; Rose, Kathryn S.; Brian Sharp, W.; Rotstein, David
Abstract The current paucity of published blood values and other clinically relevant data for short‐beaked common dolphins, Delphinus delphis, hinders the ability of veterinarians and responders to make well‐informed diagnoses and disposition decisions regarding live strandings of this species. This study examined hematologic, clinical chemistry, and physical parameters from 26 stranded common dolphins on Cape Cod, Massachusetts, in light of their postrelease survival data to evaluate each parameter's efficacy as a prognostic indicator. Statistically and clinically significant differences were found between failed and survived dolphins, including lower hematocrit, hemoglobin, TCO2, and bicarbonate and higher blood urea nitrogen, uric acid, and length‐to‐girth ratios in animals that failed. In general when compared to survivors, failed dolphins exhibited acidosis, dehydration, lower PCVs, and decreased body condition. Additionally, failed dolphins had the highest ALT, AST, CK, LDH, GGT, and lactate values. These blood values combined with necropsy findings indicate that there are likely a variety of factors affecting postrelease survival, including both preexisting illness and stranding‐induced conditions such as capture myopathy. Closer evaluation of these parameters for stranded common dolphins on point of care analyzers in the field may allow stranding personnel to make better disposition decisions in the future.